Development of S-Propranolol-Imprinted polymer composite cellulose membrane for transdermal delivery of B-blocker enantiomer - Naruedom Tangthong (Prince of Songkla University, 2007)
Thesis (M.Pharm., Pharmaceutical Sciences)--Prince of Songkla University, 2007